Factors Associated With Ambulatory Activity in De Novo Parkinson Disease. Issue 2 (April 2017) - Christiansen, Cory; Moore, Charity; Schenkman, Margaret; Kluger, Benzi; Kohrt, Wendy; Delitto, Anthony; Berman, Brian; Hall, Deborah; Josbeno, Deborah; Poon, Cynthia; Robichaud, Julie; Wellington, Toby; et al.
Abstract : Background and Purpose: Objective ambulatory activity during daily living has not been characterized for people with Parkinson disease prior to initiation of dopaminergic medication. Our goal was to characterize ambulatory activity based on average daily step count and examine determinants of step count in nonexercising people with de novo Parkinson disease. Methods: We analyzed baseline data from a randomized controlled trial, which excluded people performing regular endurance exercise. Of 128 eligible participants (mean ± SD = 64.3 ± 8.6 years), 113 had complete accelerometer data, which were used to determine daily step count. Multiple linear regression was used to identify factors associated with average daily step count over 10 days. Candidate explanatory variable categories were (1) demographics/anthropometrics, (2) Parkinson disease characteristics, (3) motor symptom severity, (4) nonmotor and behavioral characteristics, (5) comorbidities, and (6) cardiorespiratory fitness. Results: Average daily step count was 5362 ± 2890 steps per day. Five factors explained 24% of daily step count variability, with higher step count associated with higher cardiorespiratory fitness (10%), no fear/worry of falling (5%), lower motor severity examination score (4%), more recent time since Parkinson disease diagnosis (3%), and the presence of a cardiovascular condition (2%). Discussion and Conclusions: Daily step count in nonexercising people recruited for this intervention trial with de novo Parkinson disease approached sedentary lifestyle levels. Further study is warranted for elucidating factors explaining ambulatory activity, particularly cardiorespiratory fitness, and fear/worry of falling. Clinicians should consider the costs and benefits of exercise and activity behavior interventions immediately after diagnosis of Parkinson disease to attenuate the health consequences of low daily step count. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A170 ). Abstract : Supplemental Digital Content is Available in the Text.